FREIES ERMESSEN DALAM PEMERINTAHAN INDONESIA - Purnamawati, Evi; Hijawati, Hijawati (Faculty of Law, University of Palembang, 2022)
Freies Ermessen is a freedom given to state administration in the context of administering government. So that Freies Ermessen is the freedom to act on its own initiative and policy from the state administration. In line with the increasing demands for public services that must be provided by State administration for the increasingly complex socio-economic life of citizens, however, the use of Freies Ermessen must not conflict with applicable law, both written law and unwritten law.